2004
DOI: 10.1161/01.res.0000121566.01778.06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Basis of Sinus Bradycardia in Congenital Heart Block

Abstract: Abstract-Congenital heart block (CHB) is a conduction abnormality characterized by complete atrioventricular (AV) block. CHB affects fetuses and/or newborn of mothers with autoantibodies reactive with ribonucleoproteins 48-kDa SSB/La, 52-kDa SSA/Ro, and 60-kDa SSA/Ro. We recently established animal models of CHB and reported, for the first time, significant sinus bradycardia preceding AV block. This unexpected observation implies that the spectrum of conduction abnormalities extends beyond the AV node to als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…These auto-antibodies produced a similar decrease in I CaL amplitude in rat ventricular cardiomyocytes (Boutjdir et al, 1998), canine Purkinje myocytes (Qu et al, 2001), and rabbit sinoatrial cells (Hu et al, 2004). Interestingly, I CaT from rabbit sinoatrial cells is also blocked by these antibodies (Hu et al, 2004).…”
Section: Congenital Heart Blockmentioning
confidence: 80%
“…These auto-antibodies produced a similar decrease in I CaL amplitude in rat ventricular cardiomyocytes (Boutjdir et al, 1998), canine Purkinje myocytes (Qu et al, 2001), and rabbit sinoatrial cells (Hu et al, 2004). Interestingly, I CaT from rabbit sinoatrial cells is also blocked by these antibodies (Hu et al, 2004).…”
Section: Congenital Heart Blockmentioning
confidence: 80%
“…The causal relationship of positive IgG to autoimmuneassociated sinus bradycardia in CHB has been documented in animal models of CHB 4,5,11 and in clinical settings 7,8 ; however, the underlying molecular mechanism remains unknown. The candidate antigens SSA-Ro and SSB-La are intracellularly located, and there is no convincing evidence that maternal antibodies can cross the sarcolemma of a normal myocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, positive IgGsuperfused rat and rabbit hearts and pups from mice injected with positive IgG during pregnancy exhibited profound sinus bradycardia by ECG and optical action potential recordings. 4,6,11 Furthermore, we recently showed that superfusion of spontaneously beating single rabbit SA node myocytes with positive IgG resulted in significant sinus bradycardia as measured by an increase in action potential cycle length. 11 In the present study, we also unexpectedly observed expression of the ␣ 1D Ca channel in the fetal ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole cell configuration of the patchclamp technique was used for ion current recordings. Cells were first superperfused with Tyrode solution, and then the perfusion was switched to the appropriate solution for each current studied as previously described (7). All experiments were conducted at room temperature.…”
Section: Methodsmentioning
confidence: 99%